An Organic Dyad Composed of Diathiafulvalene‐Functionalized Diketopyrrolopyrrole–Fullerene for Single‐Component High‐Efficiency Organic Solar Cells. (30th August 2016) - Narayanaswamy, K.; Venkateswararao, A.; Nagarjuna, P.; Bishnoi, Swati; Gupta, Vinay; Chand, Suresh; Singh, Surya Prakash
Abstract: A new low‐band gap dyad DPP‐Ful, which consists of covalently linked dithiafulvalene‐functionalized diketopyrrolopyrrole as donor and fullerene (C60 ) as the acceptor, has been designed and synthesized. Organic solar cells were successfully constructed using the DPP‐Ful dyad as an active layer. This system has a record power‐conversion efficiency (PCE) of 2.2 %, which is the highest value when compared to reported single‐component organic solar cells.